Characterization of triple pass Erbium-doped Fiber Amplifiers - Akhter, Fowzia; Naji, Ahmed Wathik; Ibrahimy, Muhammad Ibn; Siddiquei, Hasin Reza (2012)
The main purpose of designing multi stage EDFAs is to achieve higher gain and lower Noise Figure. This paper represents all possible triple pass EDFA configurations. Performance of all the configurations has been analyzed with the pump power ratio, signal power. Optimum length and Optimum pump power ratio has also been determined for each and every configurations. From the performance analysis best triple pass EDFA has been recommended for practical design.